Histological differences in the livers and kidneys of two populations of rice frog (Fejervarya limnocharis) naturally exposed to different environmental cadmium levels - Mohd Sham Othman,; Robson, Mark Gregory; Wichase Khonsue,; Jirarach Kitana,; Kumthorn Thirakhupt,; Noppadon Kitana, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Histological observation has always been important in the study of sentinels. In this research, histological differences in the liver and kidney of two wild populations of Fejervarya limnocharis exposed to different environmental cadmium levels were observed. Liver and kidney samples from 30 rice frogs caught from reference site (Mae Pa) and contaminated site (Mae Tao) were sectioned and stained with Haemotoxylin and Eosin and then observed under light microscope. It was found that liver sections from frogs caught from Mae Tao had higher hepatic macro-melanophage count (MMC) (0.949 ± 0.267 cells/1000 μm2) as compared to those from Mae Pa (0.672 ± 0.299 cells/1000 μm2). Other observable histological features found in frog’s liver from Mae Tao include possible necrotic areas, cellular swellings and chromatin margination. The kidney sections from frogs caught from Mae Tao showed the presence of tumor-like cell aggregation and hemorrhage. However, the proportion of tumor-like cell aggregation and hemorrhage were not significantly different than were expected from random occurrences. The result of the histological study revealed that F. limnocharis caught from Mae Tao had higher hepatic MMC and higher prevalence of renal tumor-like aggregation and renal hemorrhage than the rice frogs caught from Mae Pa. Cellular swelling, possible necrotic area and possible apoptotic cell could also be observed in the liver of contaminated frogs.